The religious Riddles of the Exeter Book - Eric G. Stanley (Filologia Germanica, 2024)
Exeter Book Riddles, nos 4, 26, 43, 46, 66, 85, 90 (Latin), 95, are certainly on religious subjects, orat least probably, after consideration of proposed solutions; and this paper deals only with these eight Riddles. Usually the first significant word in each riddle guides the reader to the solution. That has not always been recognized by the scholars who have attempted to solve them. Thus in Riddle 4 the compound þragbysig, in line 1a, guides the reader to “bell”; the word is composed of ‘time’ and ‘busy’, and bells are busy at definite times to summon to divine service or to strike the canonical hours. That is a religious subject. Other solutions that have been proposed, “millstone” for example, are not subject to ‘time’. A principle of how to proceed from the beginning of a riddle to its solution is established for Riddle 4, which is discussed at greater length than any of the others. As early as 1835 Riddle 26 has been solved as “book” or more precisely “Bible codex”. Riddle 43 was solved as “soul and body” in 1859, after recognizing some wordplay that might misdirect to a heroic solution. Latin sources are often important, and Riddle 40 is based on a very long riddle by the Anglo-Saxon Latin poet Aldhelm. The proportion of religious riddles in the total of Exeter Book Riddles is relatively small, whereas in Old English poetry as a whole the proportion of religious poetry is very high. Perhaps religion was considered too serious a subject in the monasteries for the lighthearted game of setting and solving riddles.